Analisis Maqāṣid Asy-Syarī’ah Ibrahim Ibn Musa Al-Shatibi Terhadap Undang-Undang Nomor 16 Tahun 2019 Tentang Perubahan Batasan Usia Perkawinan - Waluyo Sudarmaji (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2021)
This reasearch is motivated by the amendment of law No. 1 of 1974 in article 7 paragraph (1) concerning the age limit of marriage, which was 16 (sixteen) for women and 19 (nineteen) for men which have now been changed to law No. 16 of 2019, namely the permission to carry out a marriage if a person has reached the age of 19 (nineteen) years for men and women. This reasearch was conducted to find out whether law No. 16 of 2019 is in accordance with the objectives of the shari’ah. This article research uses qualitative research combined with library research methods. Data collection was done through library studies and documents. The result of this study indicate that law No. 16 of 2019 amendments to law No. 1 of 1974 concerning the age limit of marriage has reached the goal of shari’ah (maqāṣid asy- syarī’ah) which is based on the objectives of dharuriyat al-khomsah, this is seen from the factors behind and the purpose of amending this law, namely for the benefit.